Software Testing on The Learning of Islamic Education Media Based on Information Communication Technology Using Blackbox Testing - S Sutiah; S Supriyono (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2020)
Learning Media is a set of tools that can be helpful and complementary to teachers or educators to achieve a good and righteous learning process with the learners. The development of the learning media based on Information Communication Technology is excellent in the technological era and the millennial period because it can motivate students to learn. Learning materials can be through images, video, text, and other media. The following research is conducting software testing on Islamic religious education learning media using the BlackBox testing approach. The purpose of the study is the implementation of BlackBox testing in media learning Islamic education software. The results obtained showed pretty good results with software testing accuracy of 90%. This research suggests that BlackBox testing is capable of measuring software quality.